Ergoprotective Effect of Vitamins in Toxic Liver Damage (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The introduction of hepatotropic poisons into the body of experimental rats in combination with starvation and hypothermia at the first stages increases physical performance. However, continued exposure to these factors leads to a significant decrease in performance and the development of splenocytes with inhibitory properties. The use of vitamins A and B1 separately helps to normalize performance, and their combined use neutralizes the effects of hepatotropic poisons, affecting splenocytes. Vitamins A, E, and C create a pronounced neuroprotective effect, and their combination with thiamine, carotene, and biotin improves the physical activity of rats during starvation and hypothermia. This effect is enhanced by the addition of polyunsaturated phospholipids (for example, essentiale).